Compact circularly polarized antenna based on quarter-mode substrate integrated waveguide sub-array - Li, Rui (2014)
A compact and circularly polarized planar antenna is presented in this paper based on a quarter-mode substrate integrated waveguide sub-array. The operating principle and design guidelines of the proposed antenna are discussed with the aid of an isosceles right triangular cavity with two magnetic side walls and one electric side wall. The mode solutions are determined and the resonant frequencies of the triangular cavity are calculated. The designed antenna is fabricated and its radiation characteristics are measured. Measured results are in good agreement with predicted ones. It is demonstrated that the proposed structure is a simple and compact candidate of high performance circularly polarized antenna.